Is a universal income grant an appropriate social policy to alleviate poverty in Rwanda? - Haguma, John (2014)
Masters of Commerce === Rwanda is characterised as a low-income country amongst the poorest on the African continent.Poverty in Rwanda has been persistent for a long period of time and it was made worse by the genocide that took place in 1994 and claimed over a million people. Although a variety of social policies, both home-grown and foreign, have been adopted since 1994 by the government of Rwanda to try and alleviate poverty, none has up to now succeeded to get rid of the povertyconflict trap, partly because they are all means tested. It should be noted here that Rwanda’s situation needs a universal approach in order to help ameliorate the current poverty level which is now at 60 percent, and the rising inequality. The researcher, when investigating a universal approach to use, suggested that a UIG could be the appropriate social policy option for Rwanda.Rwanda has set itself goals through its Vision 2020 and the EDPRS to have changed the country’s position by the year 2020 from being categorised as a low-income country into a middle-income country like South Africa. However, for this to be possible, economic growth must be robust. An annual growth rate of 7 percent needs to be maintained. It also means that the current per capita annual income of $290 needs to be increased to $900. The researcher concurs with these developmental goals but at the same time cautions policy makers that although growth is necessary, it should not crowd out redistributive justice.There seems to be a strong argument that development approaches which focus on income transfers are more prudent in attaining economic development and poverty reduction than those whose sole intention is to attain economic growth. Although policies that pursue economic growth usually lead to inequalities in the societies, governments should take it upon themselves to ensure that there are also counter measures that will reduce poverty at the same time.The researcher in this dissertation advocates for a universal income grant financed by an increase in indirect taxes supplemented by foreign aid as the best approach towards poverty alleviation in Rwanda. It must be noted that dependency on foreign aid is not sustainable in the long-term.There is a need to come up with measures of utilizing the already existing foreign aid in alleviating poverty and also to take care of future uncertainties when the foreign aid has been stopped.In order for Rwanda to break out of the poverty–conflict trap, it needs to adopt social policies that are geared towards alleviating poverty and assuring growth. A UIG was chosen as a social policy option that is capable of alleviating poverty.This research had three major aims. First of all it shows the possible impact of a universal income grant (UIG) in as far as the alleviation of poverty in Rwanda is concerned. Secondly it considers how a part of the existing foreign aid could be channelled into a UIG for all, with the funding effectively being recouped from those who do need support by an increase in the indirect taxes, e.g. in VAT. Thirdly develops a micro-simulation model which could show the impact of the combination of a UIG, partly being financed out of foreign aid and partly by the increases in indirect taxes, on poverty and income distribution in Rwanda. It is clear from the analysis that if the UIG is introduced in Rwanda it will have a multiplier effect when it develops social capital,stimulate aggregate spending, increase economic activity, bring investor confidence, promote economic growth and job creation and in the end alleviate poverty.